Annotated checklist of freshwater fishes from Brunei Darussalam, Borneo - Sulaiman, Zohrah; Hui, Tan Heok; Lim, Kelvin Kok Peng (Zootaxa, 2018)
The freshwater fish diversity of Brunei Darussalam is reviewed. At present, a total of 104 species of freshwater fishes from 59 genera, 24 families and 10 orders is recorded. Eight species including one introduced species and two from brackish waters present new records for Brunei. The family Cyprinidae has the highest diversity with 40 species. Forty-six species are believed to be endemic to Borneo including six species known only from Brunei Darussalam namely Barbodes xouthos, Rasbora tubbi, Gastromyzon cranbrookii, Gastromyzon venustus, Neogastromyzon brunei and Ompok platyrhynchus and three are exotics.